Environmental and human health impact of recycle concrete powder: an emergy-based LCA approach - Manan, Aneel; Pu, Zhang; Sabri, Mohanad Muayad; Alattyih, Wael; Ahmad, Jawad; Alzlfawi, Abdullah (Frontiers in Environmental Science, 2025)
The construction sector extensively utilizes natural resources and energy, contributing significantly to greenhouse gas emissions (GHG). Concrete production, in particular, contributes notably to environmental pollution. This study investigates the environmental and human health impact of concrete production, focusing on parameters such as Portland Cement, organic chemicals, diesel, medium voltage electricity, crushed gravel, natural gas heat, lubricating oil, sand and tap water. It also evaluates the impact of replacing cement with recycled concrete powder (RCP) using a life cycle assessment (LCA) approach through OpenLCA 2.1 software and the Ecoinvent database. Four concrete mixes were assessed with recycled concrete powder substitution ratios of 0, 5%, 10%, and 15%. Key indicators analyzed include climate change, human toxicity, ionising radiation, ozone depletion, photochemical oxidant formation, ecosystem quality, and resource depletion. Results show that cement is the most environmentally harmful ingredient, while RCP substitution reduces environmental impacts and resource depletion. Notably, the analysis indicates that higher RCP content leads to reduce environmental impacts. Specifically, the mix containing 15% RCP showed substantial improvements, lowering ozone depletion impacts from 100% to 90% and photochemical oxidant formation from 100% to 92%. These findings provide valuable insights for construction industry stakeholders and policymakers, supporting the advancement of more sustainable construction practices. Future research should focus on optimizing RCP content, long-term performance, and techno-economic feasibility to enhance sustainable construction practices.